A congested football calendar and the wellbeing of players: correlation between match exposure of European footballers before the World Cup 2002 and their injuries and performances during that World Cup - Ekstrand, J.; Walden, M.; Hägglund, M. (British Journal of Sports Medicine, 2004)
Objectives: To investigate the correlation between exposure of footballers in European clubs to match play in the months before the World Cup 2002 and their injuries and performances during that World Cup.